Acute respiratory failure in a 35-year-old woman following preterm vaginal delivery. (19th March 2014) - Bhandari, H M; Gorecha, M; Woodman, J
Abstract : A 35-year-old woman, a non-smoker with a normal body mass index, 'felt wheezy' and developed profound hypoxia 30 min after preterm vaginal delivery at 24+ weeks of gestation. She denied other symptoms, had no fever but was tachycardic and tachypnoeic with normal blood pressure. Pulmonary embolism, amniotic fluid embolism, cardiomyopathy, arrhythmias, sepsis and non-cardiogenic pulmonary oedema were considered as differential diagnoses. Chest X-ray showed an increased pulmonary vasculature, but the blood tests, ECG, echocardiogram and CT pulmonary angiogram were essentially normal. She was managed on a high dependency area with high-flow oxygen and intravenous antibiotics. She improved dramatically and the oxygen requirements dropped to 2 L over the next 4 h. It is plausible that this woman had acute non-cardiogenic pulmonary oedema secondary to a combination of risk factors. This case highlights the importance of a methodical and multidisciplinary approach for a prompt diagnosis and successful treatment of an acutely ill parturient.